Beyond the Apparent Banality of the Mathematics Classroom
VIII, 325 p.
Keywords: New research in mathematics education deals with the complexity of the mathematics’ classroom. The classroom teaching situation constitutes a pertinent unit of analysis for research into the ternary didactic relationship which binds teachers, students and mathematical knowledge. The classroom is considered as a complex didactic system, which offers the researcher an opportunity to gauge the boundaries of the freedom that is left with regard to choices about the knowledge to be taught and the ways of organizing the students’ learning, while giveing rise to the study of interrelations between three main elements of the teaching process the: mathematical content to be taught and learned, management of the various time dimensions, and activity of the teacher who prepares and manages the class, to the benefit of the students' knowledge and the teachers' own experience. This volume, reprinted from Educational Studies in Mathematics, Volume 59, focuses on classroom situations as a unit of analysis, the work of the teacher, and is strongly anchored in original theoretical frameworks. The contributions are formulated from the perspective of one or more theoretical frameworks but they are tackled by means of empirical investigations.